2020
DOI: 10.1016/j.isci.2020.101163
|View full text |Cite
|
Sign up to set email alerts
|

CDK7 Mediates the Beta-Adrenergic Signaling in Thermogenic Brown and White Adipose Tissues

Abstract: Cyclin-dependent kinases (CDKs) are emerging regulators of adipose tissue metabolism. Here we aimed to explore the role of CDK7 in thermogenic fat. We found that CDK7 brown adipose tissue (BAT)-specific knockout mice (Cdk7 bKO ) have decreased BAT mass and impaired b3-adrenergic signaling and develop hypothermia upon cold exposure. We found that loss of CDK7 in BAT disrupts the induction of thermogenic genes in response to cold. However, Cdk7 bKO mice do not show systemic metabolic dysfunction. Increased expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 42 publications
1
8
0
Order By: Relevance
“…A first indication of the participation of CDK7 in WAT physiology came from the transcriptome data that we generated from perigonadal white adipose tissue (pgWAT) in CDK7 fat‐specific knockout mice (http://www.ncbi.nlm.nih.gov/geo/query/acc.cgi?acc=GSE149128) [29]. Pathway analysis showed that a significant proportion of the 190 downregulated genes ( P < 0.05, log FC 0.5) that were found in the WAT of the Cdk7 aKO mice are involved in lipid metabolism (lipid synthesis, uptake and lipolysis) (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A first indication of the participation of CDK7 in WAT physiology came from the transcriptome data that we generated from perigonadal white adipose tissue (pgWAT) in CDK7 fat‐specific knockout mice (http://www.ncbi.nlm.nih.gov/geo/query/acc.cgi?acc=GSE149128) [29]. Pathway analysis showed that a significant proportion of the 190 downregulated genes ( P < 0.05, log FC 0.5) that were found in the WAT of the Cdk7 aKO mice are involved in lipid metabolism (lipid synthesis, uptake and lipolysis) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The generation of Cdk7 flox/flox and Cdk7 aKO mice was reported in a previous study [29]. Mice were maintained in a temperature-controlled animal facility with a 12-h light/12-h dark cycle and had access to standard chow (KLIBA NAFAG, no.…”
Section: Micementioning
confidence: 99%
See 2 more Smart Citations
“…Specifically, p27 inhibits complexes of CDK2 and cyclin A (ccna) or E (ccne) and has a critical function in the negative regulation of cellular growth [ 24 ]. Apart from their functions in cell cycle regulation, several studies have revealed that some CDKs may play an important role in metabolism [ 21 ] such as CDK4, CDK5 or CDK7 [ 25 , 26 , 27 , 28 ]. Furthermore, adipose tissue-related functions have also been attributed to some cell cycle regulators.…”
Section: Introductionmentioning
confidence: 99%